2022
DOI: 10.1088/2058-6272/aca581
|View full text |Cite
|
Sign up to set email alerts
|

Progress of the RF negative hydrogen ion source for fusion at HUST

Abstract: Huazhong University of Science and Technology (HUST) has developed an experimental setup of a radio frequency (RF) driven negative hydrogen ion source, aimed to investigate the physics of production and extraction of the H− ions for neutral beam injection in nuclear fusion reactors. The main design parameters of the ion source are: RF power ≤40 kW; extraction voltage ≤10 kV; accelerator voltage ≤20 kV. This paper gives an overview of the progress of the ion source with particular emphasis on some issues. The R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…been developing an RF driven negative hydrogen ion source experimental setup since 2011 [7]. In HUST negative ion source setup, the RF power needed to ignite the source plasma is possible up to 40 kW (the maximum RF power is 20 kW in the present experimental campaign).…”
Section: Introductionmentioning
confidence: 99%
“…been developing an RF driven negative hydrogen ion source experimental setup since 2011 [7]. In HUST negative ion source setup, the RF power needed to ignite the source plasma is possible up to 40 kW (the maximum RF power is 20 kW in the present experimental campaign).…”
Section: Introductionmentioning
confidence: 99%
“…Nocentini et al utilized the finite element method to design the PG and magnetic configuration, aiming to achieve a more uniform magnetic filter field distribution and thus a homogeneous plasma beam [22]. Yang et al developed a 1D particlein-cell/Monte Carlo collision (PIC/MCC) model, in which the plasma loss at the sidewall was estimated by a loss estimation model to reduce the computational cost, to study the plasma transport through a Gaussian profile magnetic field [23,24]. By using a 2D PIC model, Hatayama et al investigated the impact of magnetic field strength, and they revealed the optimal value for H − extraction [25].…”
Section: Introductionmentioning
confidence: 99%